2017
DOI: 10.18203/2320-1770.ijrcog20170500
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of perinatal outcome in women presented with first trimester vaginal bleeding: our experience

Abstract: Background: First trimester vaginal bleeding (FTVB) plays a role in occurrence of late pregnancy complications in both mother and infant. Late pregnancy outcomes in mothers and infants are the main concerns for the obstetricians. The purpose of this study was to assess the perinatal outcome of pregnancies complicated by first trimester vaginal bleeding.Methods: The present study included total 100 singleton pregnant women with history of FTVB whose pregnancy was confirmed chemically. Patients were closely obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…In study conducted by Rai P et al, 70% had spotting, 20% had moderate bleeding followed by heavy bleeding (10%). 24 This is in accordance with the study of Patel NG et al, majority (68%) had spotting, 22% had moderate bleeding followed by heavy bleeding (10%). 18…”
Section: Bleeding Characteristicssupporting
confidence: 91%
“…In study conducted by Rai P et al, 70% had spotting, 20% had moderate bleeding followed by heavy bleeding (10%). 24 This is in accordance with the study of Patel NG et al, majority (68%) had spotting, 22% had moderate bleeding followed by heavy bleeding (10%). 18…”
Section: Bleeding Characteristicssupporting
confidence: 91%
“…In study conducted by Patel et al, (2014), incidence of LBW and IUGR was 35.9% and 14.1% respectively. In study conducted by Patel et al, (2015) and Rai et al, (2017), IUGR was found in 13.6% and 14% of cases respectively. The mean birth weight in our study was 2.62 ±0.48 kg.…”
Section: Low Birth Weightmentioning
confidence: 88%
“…In our study, majority of patients had spotting (61%), light bleeding (29%) followed by heavy bleeding (10%). In study conducted by Rai et al, (2017), 70% had spotting, 20% had moderate bleeding followed by heavy bleeding (10%). This is in accordance with the study of Patel et al, (2014), majority (68%) had spotting, 22% had moderate bleeding followed by heavy bleeding (10%).…”
Section: Bleeding Characteristicsmentioning
confidence: 95%
“…The outcome is likely to be affected by the gestational age of bleeding, cause of bleeding and severity of bleeding. [1] It is also known that maternal age, systemic diseases such as diabetes mellitus, hypothyroidism, infertility treatment, thrombophilia, maternal weight and uterine structural anomalies increase the risk of abortus imminens. [2] The purpose of the study was to observe the effect of first trimester bleeding on maternal & foetal outcomes.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%